The Use of GAMLET Pictionary to Improve English Vocabulary Acquisition among a Group of ESL Learners in a Chinese National-Type School in Malaysia - Teo Woon Chun; Ramesh Sathappan (Development in Language Studies, 2024)
English vocabulary is a fundamental component of the English language and is essential for ESL learners to master. However, many ESL learners in Malaysia cannot spell English vocabulary correctly due to limited exposure to English as posited by Gu and Lornklang (2021). To address this issue, a self-directed learning module called GAMLET Pictionary was developed to help ESL learners acquire targeted vocabulary using context clues, namely definitions, visuals, and descriptions. The module is aligned with the latest format of the Final Academic Session Test (UASA), which requires pupils to understand the definition of words. GAMLET Pictionary was implemented with five pupils in a Chinese national-type primary school for a month. The findings showed that their English vocabulary mastery improved after the intervention. The findings from the questionnaire found that they held positive perceptions of GAMLET Pictionary. They enjoyed the activities designed in the module and hoped to use it to acquire more English vocabulary in the future. Overall, GAMLET Pictionary is a promising innovation that can help ESL learners improve their English vocabulary mastery. It is engaging, effective, easy to use, and aligned with the latest format of the UASA.